Media Availability and Utilization in Education Institution - Kumar, P. Ravi; Varghese, P.A. (International Journal of Social Sciences and Management, 2015)
Media plays a vital role in educational programs, health communication and agricultural development. Without a vibrant media no society can function well. The Media plays a significant role in forming and influencing people’s attitudes and behaviour. Gone are the days of chalks and blackboard and the technological changes have brought in digital projection and interactive classrooms. In this new world of interactive media networks, traditional education technology and ignorance of new media are looked down upon. In schools and colleges some of the media are used in teaching and learning. Educational media is a systematic way of designing, carrying out and evaluating the total process of learning and teaching in terms of specific objectives, based on research in human learning and communication In the present age, when scientific developments have made the human life comfortable, media education has gained much importance. Many authors and philosophers have made valuable observations about media and their utilization in schools. So, today Media is very essential tool in education institutions. Without media we can’t imagine the life of the future generation and their knowledge. In this way the present study is an effort to focus on availability of media and their utilization in education institution. In the present study researcher used the survey based on Questionnaire and Interview. Survey based on Questionnaire was used for students to get the information and Interviews were conducted with teachers and administrators of the schools. The researcher chose four schools in Bhadravathi City. The study is located in Bhadravathi Taluk of Shimoga District in Karnataka State. Two Government schools of Kannada medium and two private institutions of English medium are chosen to analyze the impact of language on education and utilizing media. The study also explain the authorities interest and teachers knowledge, weather they have a sufficient training to operate media devices, and know how to effectively link with curriculum and co-curricular activities of the school. This paper also brings out the procedural and pattern wise issues with regard to media availability and utilization in educational institutions. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 244-249 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12824